Effects of moderate intensity static magnetic fields on osteoclastic differentiation in mouse bone marrow cells. Issue 5 (30th April 2018) - Kim, Eun‐Cheol; Park, Jaesuh; Noh, Gunwoo; Park, Su‐Jung; Noh, Kwantae; Kwon, Il‐Keun; Ahn, Su‐Jin
Abstract : Although we recently demonstrated that static magnetic fields (SMFs) of 3, 15, and 50 mT stimulate osteoblastic differentiation, the effects of SMFs on osteoclastogenesis are still poorly understood. This study focused on the suppressive effects of SMFs on receptor activator of nuclear factor κB ligand (RANKL)‐induced osteoclastogenesis and bone resorption. Direct SMFs inhibit RANKL‐induced multinucleated osteoclast formation, tartrate‐resistant acid phosphatase activity, and bone resorption in mouse bone marrow‐derived macrophage cells. The conditioned medium from osteoblasts treated with SMFs also resulted in the inhibition of osteoclast differentiation as well as resorption. The RANKL‐induced expression of osteoclast‐specific transcription factors, such as c‐Fos and NFATc1, was remarkably downregulated by SMF at 15 mT. In addition, SMF inhibited RANKL‐activated Akt, glycogen synthase kinase 3β (GSK3β), extracellular signal‐regulated kinase, c‐jun N‐terminal protein kinase, mitogen‐activated protein kinase (MAPK), and nuclear factor‐κB (NF‐κB) formation. These findings indicate that SMF‐mediated attenuation of RANKL‐induced Akt, GSK3β, MAPK, and NF‐κB pathways could contribute to the direct and indirect inhibition of osteoclast formation and bone resorption. Therefore, SMFs could be developed as a therapeutic agent against periprosthetic or peri‐implant osteolysis. Additionally, these could be used against osteolytic diseases such as osteoporosis and rheumatoid arthritis. Bioelectromagnetics. 39:394–404, 2018. © 2018 Wiley Periodicals, Inc.